Product Distribution of Chemical Product Using Catalytic Depolymerization of Lignin - Damayanti Damayanti; Yeni Ria Wulandari; Ho-Shing Wu (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Lignin depolymerization is a very promising process which can generate value-added products from lignin raw materials. The main objective of lignin depolymerization is to convert the complex molecules of lignin into small molecules. Nevertheless, lignin is natural polymer which the molecules of lignin are extremely complicated due to their natural variability, and it will be a big challenge to depolymerize lignin, particularly high water yield. The various technology and methods are developed to depolymerize lignin into biofuels or bio chemical products including acid/base/metallic catalyzed lignin depolymerization, pyrolysis of lignin, hydroprocessing, and gasification. The distribution and yield of chemical products depend on the reaction operation condition, type of lignin and kind of catalyst. The reactor type, product distributions and specific chemicals (benzene, toluene, xylene, terephthalic acid) production of lignin depolymerization are intensive discussed in this review. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).